(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To access the nutritional status of children with community-acquired pneumonia aged 2-59 months at the Department of Pediatrics, Duc Giang General Hospital in 2024. Subject and methods: A cross-sectional study on 150 children with community-acquired pneumonia aged 2-59 months at the Department of Pediatrics, Duc Giang General Hospital from January 2024 to September 2024. Results: The proportion of boys and girls participating in the study was almost equal, of which 85 were boys (56.7%), 65 were girls (43.3%). Children were mainly in the age group of 2-23 months with 99 children (66%), 51 children were in the age group of 24-59 months (34%). The average weight and height of the 24-59 months group and the 2-23 months group were 12.69 ± 2.48 kg and 89.25 ± 6.79 cm, 9.06 ± 1.94 kg and 73.56 ± 7.84 cm, respectively. The children participating in the study had a rate of underweight malnutrition of 7.3%, stunting malnutrition of 18%, wasting malnutrition of 5.3%, and overweight-obese children had a rate of 7.3%. The children participating in the study had 6.0% of moderately underweight malnutrition, 1.3% of severely underweight malnutrition; 8.7% of moderately stunted malnutrition, 9.3% of severely stunted malnutrition; and 5.3% of moderately stunted malnutrition. Conclusion: Children aged 2-59 months with community-acquired pneumonia have poor nutritional status. It is necessary to assess nutritional status and have early intervention measures for children at risk of malnutrition to prevent malnutrition in children receiving inpatient treatment at the hospital.